Validation of TESS Planet Candidates with Multicolor Transit Photometry and TRICERATOPS+ - Jonathan Gomez Barrientos; Michael Greklek-McKeon; Heather A. Knutson; Steven Giacalone; W. Garrett Levine; Morgan Saidel; Shreyas Vissapragada; David R. Ciardi; Karen A. Collins; David W. Latham; Cristilyn N. Watkins; Polina A. Budnikova; et al. (The Astronomical Journal)
We present an upgraded version of TRICERATOPS , a software package designed to calculate false positive probabilities for planet candidates identified by the Transiting Exoplanet Survey Satellite (TESS). This enhanced framework now incorporates ground-based light curves in separate bandpasses, which are routinely obtained as part of the candidate vetting process. We apply this upgraded framework to explore the planetary nature of 14 TESS planet candidates, combining primarily J- band light curves acquired with the 200 inch Hale Telescope at Palomar Observatory with complementary archival observations from the Las Cumbres Observatory Global Telescope, the Fred Lawrence Whipple Observatory, and the Teide Observatory, along with existing TESS data and contrast curves from high-resolution imaging. As a result of this analysis we statistically validate (false positive probability < 1.5% and nearby false positive probability < 0.1%) six new planets in five systems: TOI-1346 b, TOI-1346 c, TOI-2719 b, TOI-4155 b, TOI-6000 b, and TOI-6324 b. For these systems, we provide updated estimates of their stellar and planetary properties derived from the TESS and ground-based observations. These new systems contain planets with radii between 0.9 and 6 R _⊕ and orbital periods between 0.3 and 5.5 days. Finally, we use our upgraded version of TRICERATOPS to quantify the relative importance of multiwavelength transit photometry and high-resolution imaging for exoplanet candidate validation, and discuss which kinds of candidates typically benefit the most from ground-based multicolor transit observations.